Kendala Aksesibilitas Pembiayaan Usaha Mikro Kecil Dan Menengah (UMKM) Dari Lembaga Keuangan - Indra Mualim Hasibuan; Marliyah (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a vital role in encouraging the development of the country's economy, including contributing to GDP and employment. However, even though MSMEs' contribution to the economy is very central, MSMEs still face several obstacles such as difficult access to financing from financial institutions. The aim that researchers want to achieve in this research is to describe what factors hinder the accessibility of MSMEs to financial institutions, especially banks, and to find out the solutions provided by the government to overcome obstacles to MSMEs' accessibility to financing. This research category is qualitative research with a library study approach, where research data sources are accessed from various literature or documents. Based on research by researchers, there are several factors that hinder the accessibility of MSMEs, including: MSMEs in the eyes of banking financial institutions are not yet bankable, understanding of MSME actors, lack of financial literacy of MSME actors, and complicated financing procedures.